2019
DOI: 10.3389/fncir.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

A New Projection From the Deep Cerebellar Nuclei to the Hippocampus via the Ventrolateral and Laterodorsal Thalamus in Mice

Abstract: The cerebellar involvement in cognitive functions such as attention, language, working memory, emotion, goal-directed behavior and spatial navigation is constantly growing. However, an exact connectivity map between the hippocampus and cerebellum in mice is still unknown. Here, we conducted a tracing study to identify the sequence of transsynaptic, cerebellar-hippocampal connections in the mouse brain using combinations of Recombinant adeno-associated virus (rAAV) and pseudotyped deletion-mutant rabies (RABV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 73 publications
4
74
0
3
Order By: Relevance
“…; Bohne et al . ), and we see no fibres from fastigial neurons in the hippocampus in our virally injected animals (data not shown). This suggests that other downstream pathways engaged by cerebellar stimulation must underlie hippocampal seizure attenuation (for a review, see Yu & Krook‐Magnuson, ).…”
Section: Discussionmentioning
confidence: 63%
“…; Bohne et al . ), and we see no fibres from fastigial neurons in the hippocampus in our virally injected animals (data not shown). This suggests that other downstream pathways engaged by cerebellar stimulation must underlie hippocampal seizure attenuation (for a review, see Yu & Krook‐Magnuson, ).…”
Section: Discussionmentioning
confidence: 63%
“…This is in contrast with the traditional view associating the cerebellum exclusively with motor coordination and learning, but supported by more recent studies, which have revealed a role for the cerebellum in cognitive functions such as attention, language, working memory, emotion, and in visuospatial navigation (Timmann and Daum, 2007;Baillieux et al, 2008;Timmann et al, 2010). Viral tracer studies have recently demonstrated previously unknown connections between the cerebellum and hippocampus -in particular a polysynaptic circuit from the cerebellar fastigial nucleus with a thalamic relay in the LDDM/LDVL and VL, which in turn synapses on the subiculum, retrosplenial cortex, and rhinal cortex, which all project to the hippocampus (Bohne et al, 2019). These connections are indicative of a role in spatial navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the basolateral amygdaloid complex (BLA) integrates information regarding fear and anxiety-inducing stimuli, regulating emotional and behavioral responses ( 20 ). Furthermore, the BLA receives sensory information, such as vestibular outputs, through axons networking through the superior and lateral vestibular nuclei, which then project through the thalamic nuclei to the BLA ( 21 ). Evidence linking pathological dysfunction of the amygdala and thalamus to sensory impairments is important to further understanding the mechanisms associated with bTBI.…”
Section: Introductionmentioning
confidence: 99%